MENGANALISIS RESPON SISWA TERHADAP PEMBELAJARAN MATERI PERBANDINGAN DAN SKALA MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Yogi Mardianto; Lilit Abdul Azis; Risma Amelia (IKIP Siliwangi, 2022)
The purpose of this study was to analyze student responses to comparative and scale learning materials using a contextual approach. In this study using descriptive qualitative research methods. The subjects in this research are seventh grade students of Junior High School in one of the State Junior High Schools in Cianjur Regency. The data collection technique used is through a closed student response questionnaire using a Likert scale in its processing based on the characteristics of the contextual approach. There are 6 indicators with ten positive statements and ten negative statements. The questionnaire data processing technique begins with calculating the frequency of respondents choosing SS (Strongly Agree), S (Agree), TS (Disagree), and STS (Strongly Disagree) on each positive and negative statement. After that, add up the scores for each statement and then take the average percentage so that the student response criteria can be determined. The results of this study indicate that student responses to learning comparative and scale materials using a contextual approach are categorized as positive, with an average score of 83%. This result is very visible during the learning process students are more active, have self-confidence, have high enthusiasm and curiosity.